Pressure pain thresholds and tender point counts as predictors of new chronic widespread pain in somatising subjects. Issue 4 (29th September 2006) - Gupta, A; McBeth, J; Macfarlane, G J; Morriss, R; Dickens, C; Ray, D; Chiu, Y H; Silman, A J
Abstract : Background: : Tender points are a general measure of distress both in the community and in clinic subjects. It has been suggested that multiple tender points should be regarded as the early stages of somatisation of distress. Similarly, recent evidence suggests that chronic widespread pain (CWP) is one manifestation of the somatisation of distress. Objective: Given that a high tender point count and CWP are clinical hallmarks of the fibromyalgia syndrome, it was hypothesised that in somatising subjects, a high tender point count or a low pain threshold would predict the development of CWP in the future. Methods: In this population-based prospective study, 245 adults aged 25–65 years, free of CWP, were identified on the basis of a detailed questionnaire on pain and a psychosocial questionnaire comprising the Somatic Symptom Checklist and the Illness Behaviour subscale of the Illness Attitude Scales. These subjects took part in a pain threshold examination with a Fischer pressure algometer. Tender point counts were computed by including all areas with a pain threshold <4 kg/cm 2 . Individuals were followed up at 15 months, at which time 231 (93% of subjects still living at their baseline address) provided data on pain status, using the same instruments. Results: At follow-up, 26 (11%) subjects developed new CWP. Although subjects with a low baseline pain threshold were not at increased risk of developing symptoms, a high tender point count, adjusted for age, sex, baseline pain status and other confounding factors, predicted the development of new CWP. Conclusion: Subjects free of CWP are at an increased risk of its development if they have a high tender point count. However, a low-pressure pain threshold does not predict the onset of symptoms. Data from this population-based prospective study suggest that a low pain threshold in subjects with CWP is likely to be a secondary phenomenon as a result of pain or associated distress rather than the antecedent of symptoms.